Searching for Antibiotic Resistance Genes in a Pristine Arctic Wetland. (April 2017) - Diaz, Krystalle S.; Rich, Virginia I.; McLain, Jean E.
Abstract: Antibiotics are the foundation of modern medicine, and the sustainability of antibiotic use depends on overcoming the challenge of antibiotic resistance (AR). This may be extremely difficult, given that antibiotic production by environmental microbiota is a natural process and AR is widespread in nature. AR has been shown to spread readily and quickly, as well as to exist in the absence of anthropogenic forcing (i.e., the application of antibiotics by humans). This study compared a range of approaches to identify AR gene sequences in microbial community genomes in three habitats (Palsa, Bog, and Fen) across a permafrost thaw gradient in Abisko, Sweden. Depending on the search algorithm used, we found a range of 0.72–1.29% AR protein‐coding genes across all habitats, with model‐based search algorithms resulting in greater sensitivity than traditional identity‐based approaches for identifying AR sequences. Though each habitat within the permafrost gradient showed different cell densities, pH, bioavailable carbon, water content, nutrient availability, and other factors that impact microbial life, the difference in overall AR protein abundance between habitats was not significant. Examination of AR at this location will contribute to our understanding of AR presence in natural environments and how AR may be impacted by permafrost thawing related to global warming.